Probiotics and Prebiotics: Role in Prevention of Nosocomial Sepsis in Preterm Infants - Vrinda Nair; Amuchou S. Soraisham (International Journal of Pediatrics)
Nosocomial sepsis is associated with increased mortality and morbidity including neurodevelopmental impairment and prolonged hospital stay. Prevention of sepsis especially in the preterm infants in the neonatal intensive care unit remains a major challenge. The gastrointestinal tract is an important source of potential pathogens causing nosocomial sepsis as the immature intestinal epithelium can permit translocation of bacteria and yeast. The intestinal tract and its microflora play an important role in the immunity. Altering the gut microflora has been extensively studied for immunomodulation in preterm infants. Probiotics are live microorganisms which when administered in adequate amounts confer a health benefit on the host. Probiotics have been used for prevention and treatment of various medical conditions in children and adults. Studies on probiotics in premature infants have focused on normalizing intestinal flora, improvement in feeding intolerance, prevention of necrotizing enterocolitis and sepsis. In this paper, we discuss the intestinal bacterial colonization pattern; the rational for probiotics and prebiotic therapy with special focus on the prevention of nosocomial sepsis in preterm infants.